The Importance of the Cluster Method of Production in Agriculture - G.Xalmatjanova; F.Sadikova (Zien Journals, 2022)
The article analyzes the possibility of processing raw materials grown in a cluster way, delivering it to the consumer in the form of finished products
Keywords: cluster; agriculture; value chain; fruit and vegetable growing